Diagnosis and treatment of eating disorders in children and adolescents - Ana Paola Robatto; Carla de Magalhães Cunha; Luiza Amélia Cabus Moreira (Elsevier, 2024)
Objectives: To provide a narrative review of the main eating disorders (ED), specifically focusing on children and adolescents. This review also aims to help the pediatrician identify, diagnose, and refer children and adolescents affected by this medical condition and inform them about the multidisciplinary treatment applied to these disorders. Data source: The research was conducted in the Scientific Electronic Library Online (SciELO), Medical Literature Analysis and Retrieval System Online (Medline) databases via PubMed and Embase. Consolidated Guidelines and Guidebooks in the area were also included in the review to support the discussion of ED treatment in childhood and adolescence. Data synthesis: ED are psychiatric condition that usually begins in adolescence or young adulthood but can occur at any time of life, including in childhood, which has been increasingly frequent. Pediatricians are the first professionals to deal with the problem and, therefore, must be well trained in identifying and managing these disorders, which can be severe, and determine physical complications and quality of life of patients and their families. Conclusion: ED has shown an increase in prevalence, as well as a reduction in the age of diagnosed patients, requiring adequate detection and referral by pediatricians. The treatment requires a specialized multidisciplinary team and is generally long-lasting for adequate recovery of affected individuals.